2009
DOI: 10.1161/hypertensionaha.108.127100
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential Vanilloid Type 4–Deficient Mice Exhibit Impaired Endothelium-Dependent Relaxation Induced by Acetylcholine In Vitro and In Vivo

Abstract: Abstract-Agonist-induced Ca 2ϩ entry is important for the synthesis and release of vasoactive factors in endothelial cells. The transient receptor potential vanilloid type 4 (TRPV4) channel, a Ca 2ϩ -permeant cation channel, is expressed in endothelial cells and involved in the regulation of vascular tone. Here we investigated the role of TRPV4 channels in acetylcholine-induced vasodilation in vitro and in vivo using the TRPV4 knockout mouse model. The expression of TRPV4 mRNA and protein was detected in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
189
3
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(214 citation statements)
references
References 35 publications
18
189
3
4
Order By: Relevance
“…This is also consistent with old observations that the resting level of cGMP falls after removal of external Ca 2+ (White & Martin, 1989). In other studies, it has been shown that the TRPV4-mediated Ca 2+ signal was required for eNOS activation by ACh (Adapala et al, 2011;Zhang et al, 2009), also illustrating the necessity of Ca 2+ influx for endothelial NO release. Isshiki et al (Isshiki et al, 2004) suggested that agonist-stimulated eNOS activity in the endothelial cells was sensitive to external Ca 2+ -dependent acute changes in intracellular subcortical Ca 2+ signals and that basal eNOS activity was maintained and regulated by subplasmalemmal Ca 2+ equilibrated with extracellular Ca 2+ .…”
Section: Phenylephrine-induced Contractions and Nosupporting
confidence: 92%
“…This is also consistent with old observations that the resting level of cGMP falls after removal of external Ca 2+ (White & Martin, 1989). In other studies, it has been shown that the TRPV4-mediated Ca 2+ signal was required for eNOS activation by ACh (Adapala et al, 2011;Zhang et al, 2009), also illustrating the necessity of Ca 2+ influx for endothelial NO release. Isshiki et al (Isshiki et al, 2004) suggested that agonist-stimulated eNOS activity in the endothelial cells was sensitive to external Ca 2+ -dependent acute changes in intracellular subcortical Ca 2+ signals and that basal eNOS activity was maintained and regulated by subplasmalemmal Ca 2+ equilibrated with extracellular Ca 2+ .…”
Section: Phenylephrine-induced Contractions and Nosupporting
confidence: 92%
“…Although the cellular mechanisms linking membrane receptors to TRPV4 opening are still unclear, UTP utilizes PLA2 to gate the channel [297] , while PKCα mediates Ach-dependent activation [307] . Despite the evidence for TRPV4-evoked vasodilation, the baseline blood pressure is not affected in TRPV4 -/-mice [305,306] . Nevertheless, systemic activation of the channel may induce vasorelaxation in vivo [302,303,308,309] and, eventually, lead to circulatory collapse [303] .…”
Section: Trpv2mentioning
confidence: 85%
“…TRPC3-and TRPC6-induced Ca 2+ inflow underpin the stimulatory effect of VEGF on endothelial proliferation, migration and permeability [18,231,236] , while ATP exploits TRPC3 to activate NF-κB and increase vascular cell adhesion molecule-1 expression [237] . TRPC3-driven NO synthesis and vasore- TRPV1 TRPV2 TRPV3 TRPV4 TRPV5 TRPV6 PCa/PNa and conductance (pS) [202] 10, 35-80 1-3, NM 12, 172 6, 90 > 100, 75 > 100, 40-70 Human coronary artery ECs [300] (+RT-PCR, WB, IHC) Human pulmonary artery ECs [415] +(RT-PCR) +(RT-PCR) +(RT-PCR) Human pulmonary microvascular ECs +(RT-PCR) Human cerebral microvascular ECs [272] +(RT-PCR, IC) Human cerebral arterioles ECs [305] +(RT-PCR, IHC) Human dermal microvascular ECs [319] +(RT-PCR, WB) Breast cancer derived microvascular ECs [319] +(RT-PCR, WB) Human umbilical vein ECs [227,277,296,301] +(RT-PCR) +(WB, IHC) Mouse aortic ECs [280,285,299,306] +(WB) +(RT-PCR, WB, NM, IHC) Mouse pulmonary artery ECs [313] +(WB, IHC) Mouse mesenteric artery ECs [27,280,302] +(RT-PCR, WB, IC) +(RT-PCR, IC) Mouse cerebral microvascular ECs +(RT-PCR) +(RT-PCR, WB) +(RT-PCR) Mouse dermal microvascular ECs [307] +(RT-PCR, WB) Mouse carotid artery ECs [290,296] +(IHC) Rat mesenteric artery ECs [226,275,302] +(WB) +(WB, IC, IHC) Rat femoral artery ECs [312] +(RT-PCR, IC) Rat pulmonary artery ECs [303] +(WB, IHC) Rat renal artery ECs [303] +(IHC) Rat cardiac microvascular ECs [303,…”
Section: A Drop In Luminal Camentioning
confidence: 99%
See 1 more Smart Citation
“…Knockout of the key structural protein caveolin-1 appears to ablate EDHF-mediated relaxation by disrupting Ca 2+ -signaling involving TRPV4 and thus reducing connexin expression, 49 whereas TRPV4-deficient mice also lose EDHF relaxation, have reduced NO-relaxation and decreased blood pressure reduction to systemic ACh. 50 …”
Section: Endothelium-dependent Hyperpolarizationmentioning
confidence: 99%